Injury Epidemiology: The Neglected Chapter (Nepal Journal of Epidemiology, 2012)
Injuries are the significant public health problem and posing as the mounting global crisis upsetting families and communities across population levels. We need a multidisciplinary approach embedded in injury surveillance. A sensitization revolution is vital at all the health care levels to gather critical strength of dedicated personnel in the field of research in injury intervention.DOI: http://dx.doi.org/10.3126/nje.v2i4.7825 Nepal Journal of Epidemiology Vol.2(4) 2012 pp.216-218